INCUBADORAS TECNÓLOGICAS DE COOPERATIVAS POPULARES: ATUANDO A PARTIR DA EXTENSÃO UNIVERSITÁRIA - Louise de Lira Roedel Botelho (Universidade Federal de Santa Catarina, 2016)
This work is a result of research on the mapping of techno - social Incubators Cooperatives (ITCP) held in southern Brazil, which aims to analyze the current situation of these. The methodology used for this research was the method of integr ative literature review followed by mapping data from incubators, construction and qualification of a quantitative questionnaire. The questionnaire was applied in incubators of southern Brazil where they were analyzed and processed the responses of ITCPs o f Rio Grande do Sul in a Calc spreadsheet free of LibreOffice software. Through research, it was observed that the enterprises incubated in ITCPs face difficulties at the beginning of incubation, especially regarding the financing costs. It was also found that many enterprises do not have incubated legalization of their activities. It was observed that the main line of action of the incubated enterprises are the Solidarity Economy, Cooperatives and Family Agriculture. The data obtained from this research ar e of great importance to assess the current status of the Rio Grande do Sul ITCPs, but requires a deepening in future research to qualitatively understand the situation and how it can be improved.